Testing nonlinear convergence in Malaysia - Muzafar Shah Habibullah; A.M., Dayang-Affizah; Venus, Khim-Senliew; Kian, Ping Lim (Penerbit Universiti Kebangsaan Malaysia, 2013)
The purpose of the present paper is to examine income convergence in Malaysia by applying the nonlinear unit root test presented by Kapetanios et al. (KSS 2003) and extended by Chong et al. (CHLL 2008) to permit the test of long-run convergence and catching-up hypotheses. The KSS-CHLL nonlinear unit root is applied to the test of nonlinear convergence between thirteen states with respect to Wilayah Persekutuan, the richest state of Malaysia, for the period of 1965 to 2003. Generally, the results suggest that out of the thirteen states, Kedah, Negeri Sembilan, Perak, Perlis and Selangor support the long-run convergence hypothesis; while Johor, Kelantan, Melaka, Pahang and Penang suggest catching-up. Lastly, Sabah, Sarawak and Terengganu indicate income divergence from Wilayah Persekutuan.